Identification of pterygium-related mRNA expression profiling by microarray analysis - Liu, J (Eye (Lond), 2017)
PURPOSE: Pterygium is a common degenerative and proliferative disease of the ocular surface. In some severe cases, pterygium may lead to irregular corneal astigmatism and corneal stromal scarring with visual impairment. The proliferative capacities of pterygial cells make them appear similar to tumorigenesis. Although considerable progress has been made towards understanding the etiology of the disease, the pathogenesis of pterygium has not been completely understood. In our previous study, we constructed pterygium-related lncRNA libraries by using microarray to investigate the potential roles of lncRNAs in pterygium. In this study, our objective was to explore the role of mRNA in pterygium. PATIENTS AND METHODS: In this study, we constructed pterygium-related mRNA libraries by using microarray to investigate the potential roles of mRNAs in pterygium. Quantitative real-time PCR (qRT-PCR) was performed to validate some of the deregulated mRNAs in 10 patients. RESULTS: A total of 1485 upregulated and 2978 downregulated mRNAs were identified in pterygium tissues compared with paired adjacent normal conjunctival tissues (log fold change>2.0). qRT-PCR was performed to validate four overregulated and two underregulated mRNAs in 10 patients. CONCLUSIONS: Our results reveal differentially expressed mRNAs in pterygium and suggest that mRNAs may be the novel molecular targets for therapy of pterygium.